2015
DOI: 10.1177/0009922815570613
|View full text |Cite
|
Sign up to set email alerts
|

Missed Appointments

Abstract: Efforts to decrease no-show rates should target older patients and well child visits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
65
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 19 publications
6
65
0
1
Order By: Relevance
“…12 Additional causes include the wrong beliefs of the patient about the disease or the test, 13 long waiting time between the actual and scheduled appointment, insurance coverage, language and transportation difficulties. 14 Studies also suggested that reasons can differ depending on the type of healthcare settings and nature of medical tests. For instance, it was found that the high no-show rate in the mammography department is affected due to the anxiety and discomfort of patients.…”
Section: Literature Review No-show Rate and Underlying Reasonsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Additional causes include the wrong beliefs of the patient about the disease or the test, 13 long waiting time between the actual and scheduled appointment, insurance coverage, language and transportation difficulties. 14 Studies also suggested that reasons can differ depending on the type of healthcare settings and nature of medical tests. For instance, it was found that the high no-show rate in the mammography department is affected due to the anxiety and discomfort of patients.…”
Section: Literature Review No-show Rate and Underlying Reasonsmentioning
confidence: 99%
“…15 Furthermore, missing a scheduled appointment causes a minimized access for other patients, this can create dissatisfaction among patients and healthcare providers, and suboptimal care results. 14 In addition to no-show harms discussed above, a high no-show rate involves a lost revenue and thus profit to the hospital. For instance, a research conducted in a vascular laboratory found that a no-show rate of 12% can cost the laboratory a gross loss of $89,107 annually.…”
Section: Impact Of No-showsmentioning
confidence: 99%
“…A fourth barrier for parents' engagement is associated with practicalities. Researchers in the related fields of child mental health (Kazdin et al 1997) and paediatric primary care services (Samuels et al 2015) have explored why families were unable to attend an appointment; the most frequently stated reasons include trouble getting time off work, oversleeping and transportation. Greater distances from the clinic venue have also been shown to predict non-attendance (Gordon et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Frequent cancellations or “no-shows” for scheduled appointments may also be contributing to underutilization of PAVs in this population. Patient-reported barriers to attending appointments include long waiting times, 25 logistical barriers such as transportation or time off work, 26 and forgetting appointments. 26 …”
Section: Discussionmentioning
confidence: 99%